X linked alpha thalassaemia/mental retardation: spectrum of clinical features in three related males. - Wilkie, A; Gibbons, R; Higgs, D; Pembrey, M (1991)
We describe three males (two brothers and a cousin) who have the X linked alpha thalassaemia/mental retardation (ATR-X) syndrome. The diagnosis, originally suspected in the brothers because of similarity in dysmorphic features to previous cases, was confirmed haematologically in the surviving brother. The cousin has less typical dysmorphism and a virtually normal routine blood count, but haemoglobin H inclusions were found in his red blood cells showing that he has the same condition. This report expands the clinical phenotype of the ATR-X syndrome and emphasises that a normal blood count does not exclude the diagnosis.